1991
DOI: 10.1080/01652176.1991.9694300
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a sulphamethoxazole/trimethoprim formulation in pigs after intravenous administration

Abstract: SUMMARY. Plasma disposition, metabolism, protein binding and renal clearance of sulphamethoxazole (SMZ) and trimethoprim (TMP) were studied in four pigs after intravenous administration at a dose of 40 and 8 mg/kg, respectively. SMZ and TMP were quickly eliminated (mean elimination half-lives: 2.7 and 2.4 h, respectively). SMZ was predominantly acetylated; no hydroxy and glucuronide derivates could be detected in plasma and urine. TMP was 0-demethylated into 4-hydroxytrimethoprim (M I) and 3-hydroxytrimethopri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…The plasma concentration of TMP was maintained at 10.5 l m in the rat study (Takubo et al 2000a). Literature data indicate that the mean ratio of TMP concentration in kidney and plasma (C kidney }C plasma ) was about 10 in the elimination phase after rats received intravenous dose of TMP, and that the unbound fraction of TMP, as determined from the extent of its plasma protein binding, is 0.65 (Tu et al 1989;Nouws et al 1991;Gustafsson et al 1999). Based on these values, the ratio of the CLr was predicted to be 0.288, similar to the ratio observed in the rat study in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…The plasma concentration of TMP was maintained at 10.5 l m in the rat study (Takubo et al 2000a). Literature data indicate that the mean ratio of TMP concentration in kidney and plasma (C kidney }C plasma ) was about 10 in the elimination phase after rats received intravenous dose of TMP, and that the unbound fraction of TMP, as determined from the extent of its plasma protein binding, is 0.65 (Tu et al 1989;Nouws et al 1991;Gustafsson et al 1999). Based on these values, the ratio of the CLr was predicted to be 0.288, similar to the ratio observed in the rat study in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…In pigs, the main metabolic pathway for most sulfonamides is supposed to be N-acetylation (Vree et al, 1985a;Kinabo & Nielsen, 1986;Rehm et al, 1986;Nouws et al, 1989Nouws et al, , 1991Shimoda et al, 1990)). The rate and extent of the in vivo acetylation of sulfonamides is dependent on the structure of the sulfonamide.…”
mentioning
confidence: 99%
“…Furthermore, it was shown that after administration of N4-acetyl sulfonamides to humans and food-producing animals the compounds were partly deacetylated to the parent sulfonamide (Vree et al, 1985b;Nouws et al, 1989;Shimoda et al, 1990). The main metabolic pathway for TMP in pigs is Odemethylation with subsequent conjugation Gyrd-Hansen et al, 1984;Nouws et al, 1991). Two hydroxy metabolites are formed, 3'-and 4'-demethyl trimethoprim (also referred to as M4 and M1, respectively), which are glucuronidated and sulfated.…”
mentioning
confidence: 99%
“…The latter process probably contributes to ion trapping in the rumen, which may occur in the case of a weak organic base (Baggot, 1980) such as trimethoprim (Knoppert et al, 1988). Page et al (1991) have reported that there are similarities between horses and elephants in the metabolism of trimethoprim. According to Friis et al (1984) the metabolism of trimethoprim is the main factor in its elimination.…”
Section: Discussionmentioning
confidence: 99%